Identification and validation of differentially expressed genes in intramuscular fat metabolism in Guizhou yellow chickens using RNA-Seq analysis - Yingping Tian; Xiaoya Wang; Yongchao Rao; Xiaohong Zhou; Yaozhou Jiang; Qinsong Liu; Sheng Wu; Fuping Zhang (PLoS ONE, 2025)
Intramuscular fat (IMF) content is crucial for meat quality, and genetic, environmental, and nutritional factors influence its deposition. This study aims to identify genes involved in the regulation of IMF deposition in Guizhou Yellow Chickens. Thirty Guizhou Yellow Chicken hens aged 120 days were selected, and their IMF content was measured using the Soxhlet extraction method. The IMF content was divided into a high IMF group (H group, n = 4) and a low IMF group (L group, n = 4). RNA-seq was performed on the H and L groups to screen out signaling pathways and key genes that affect IMF deposition. A total of 259 differentially expressed genes(DEGs) were screened, including 195 that were up-regulated and 64 that were down-regulated. Critical genes such as COL1A1, COL1A2, COL6A3, PLTP, LPIN1, ITGA8, and FN1 were identified as key influencers of IMF deposition in Guizhou Yellow Chickens. The slow virus interference vector has demonstrated that interfering with COL1A1 can inhibit the proliferation ability of chicken preadipocytes and reduce lipid droplet accumulation. In addition, interference with COL1A1 significantly inhibited the expression of PLTP, ABHD6, LPIN1, and PTGS2 and decreased the levels of triglycerides and cholesterol at 4 and 8 days. The results further showed that COL1A1 is a key gene in the gene regulatory network during fat deposition, and the interaction of these genes affects the proliferation and differentiation of fat cells, thereby reducing the accumulation of fat droplets in muscle fibers. This study indicates that the COL1A1 gene is associated with IMF formation in Guizhou Yellow Chickens, providing a critical gene for selecting markers to control IMF formation and laying a foundation for future poultry meat quality breeding.